2020
DOI: 10.1371/journal.pone.0230242
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to sexually explicit media in early adolescence is related to risky sexual behavior in emerging adulthood

Abstract: BackgroundSexually explicit media exposure during early adolescence has been found to be associated with risky sexual behavior. However, previous study suffered from methodological issue, such as selection bias. Furthermore, little is known about the effect of multi-modality sexually explicit media exposure on risky sexual behavior, and how this relationship can be applied to non-western societies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 115 publications
2
47
1
2
Order By: Relevance
“…This finding is in line with a longitudinal study in Taiwan, which concluded that the younger an individual is exposed to sexually (pornography) contained media, the earlier the individuals would engage in sexual debut, unsafe sex, and have multiple sexual partners. 17 Photographs became the form of pornographic materials mostly accessed for the first time by students. It was different from the results of a previous study, which found that video was the pornographic material mostly seen for the first time by students in DKI Jakarta and Banten.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with a longitudinal study in Taiwan, which concluded that the younger an individual is exposed to sexually (pornography) contained media, the earlier the individuals would engage in sexual debut, unsafe sex, and have multiple sexual partners. 17 Photographs became the form of pornographic materials mostly accessed for the first time by students. It was different from the results of a previous study, which found that video was the pornographic material mostly seen for the first time by students in DKI Jakarta and Banten.…”
Section: Discussionmentioning
confidence: 99%
“…The emphatic role of print media (newspapers and magazines) in disseminating information on sexual health issues is imperative. Nevertheless, studies across the globe indicate a mixed role of media in generating sexual health awareness and related practices (Keating et al, 2006; Kumar et al, 2012; L’Engle et al, 2006; Lin et al, 2020). Adolescents living in media saturated environment are generally prone toward risky sexual behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Constant peer pressure enhances the problem further. The level of vulnerability enhances with their lack of sex education including awareness on STD contacts and its prevention (Berman & Hein, 1997; Lin et al, 2020; Pegu & Gaur, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the study, only 2624 adolescents (Mage = 13.3 ± 0.47 years) in the 7th grade (wave 1) who replied partially to the questions about gender contentedness, pubertal timing, and sexually relevant questions were deemed valid for the analysis. Subjects were followed annually until 2009 (wave 9), although some waves were not exactly one year apart [27].…”
Section: Methodsmentioning
confidence: 99%